Supplemental oxygen and exercise ability in chronic obstructive airways disease. Issue 12 (December 1988) - Davidson, A C; Leach, R; George, R J; Geddes, D M
Abstract : The influence of supplemental oxygen on exercise performance was assessed in 17 patients with severe airflow obstruction. Exercise capacity was measured by the six minute walking distance, by an endurance walking test, and by an endurance cycling test and comparison was made with performance when the patient was breathing air. In addition, the relation between the flow rate of supplemental oxygen and cycling endurance time was studied. Portable oxygen (41 min-1) carried by the patient increased the mean endurance walking time by 59% and the six minute walking distance by 17%. The endurance time for cycling at a constant work load was increased by 51% with oxygen at a flow rate of 21 min-1, by 88% at 41 min-1, and by 80% at 61 min-1. Supplemental oxygen prolonged the length of time that the patients were able to walk at a fixed speed. It also increased the mean speed achieved during a six minute walk but this was variable and did not occur in all the subjects. The benefit from supplemental oxygen was not cancelled by the effort of carrying the portable cylinder.